Implementation of School Diabetes Care in the United States: A Scoping Review. (February 2022) - An, Ruopeng; Li, Danyi; Cole, Marjorie; Park, Katherine; Lyon, Aaron R.; White, Neil H.
Diabetes management at school demands close collaboration of multiple stakeholders, including students with diabetes and parents, school nurses, teachers/staff, and local health care providers. This scoping review identified and synthesized evidence concerning factors that contributed to the quality and effectiveness of diabetes care implementation in U.S. K-12 schools. Forty-six studies met the eligibility criteria and were included. Five common factors emerged surrounding training and experiences, communications, parent engagement, resource allocations, and school environment. Complex interactions between multiple stakeholders jointly determined the quality of school diabetes care. A conceptual model was established to elucidate the complex interactions between multiple stakeholders and the relevant facilitators and barriers. Future research should improve sample representativeness, contrast school diabetes care practices to the national guidelines, and assess the impact of the social, economic, and political environment at federal, state, local/district levels on school diabetes care implementation.